Global prevalence of 4 neglected foodborne trematodes targeted for control by WHO: A scoping review to highlight the gaps - Rachel Tidman; Kaushi S. T. Kanankege; Mathieu Bangert; Bernadette Abela-Ridder (Public Library of Science (PLoS), 2023)
Background Foodborne trematodiases (FBTs) are a group of trematodes targeted for control as part of the World Health Organization (WHO) road map for neglected tropical diseases from 2021 to 2030. Disease mapping; surveillance; and capacity, awareness, and advocacy building are critical to reach the 2030 targets. This review aims to synthesise available data on FBT prevalence, risk factors, prevention, testing, and treatment. Methods We searched the scientific literature and extracted prevalence data as well as qualitative data on the geographical and sociocultural risk factors associated with infection, preventive/protective factors, and methods and challenges of diagnostics and treatment. We also extracted WHO Global Health Observatory data representing the countries that reported FBTs during 2010 to 2019. Results One hundred and fifteen studies reporting data on any of the 4 FBTs of focus (Fasciola spp., Paragonimus spp., Clonorchis sp., and Opisthorchis spp.) were included in the final selection. Opisthorchiasis was the most commonly reported and researched FBT, with recorded study prevalence ranging from 0.66% to 88.7% in Asia, and this was the highest FBT prevalence overall. The highest recorded study prevalence for clonorchiasis was 59.6%, reported in Asia. Fascioliasis was reported in all regions, with the highest prevalence of 24.77% reported in the Americas. The least data was available on paragonimiasis, with the highest reported study prevalence of 14.9% in Africa. WHO Global Health Observatory data indicated 93/224 (42%) countries reported at least 1 FBT and 26 countries are likely co-endemic to 2 or more FBTs. However, only 3 countries had conducted prevalence estimates for multiple FBTs in the published literature between 2010 to 2020. Despite differing epidemiology, there were overlapping risk factors for all FBTs in all geographical areas, including proximity to rural and agricultural environments; consumption of raw contaminated food; and limited water, hygiene, and sanitation. Mass drug administration and increased awareness and health education were commonly reported preventive factors for all FBTs. FBTs were primarily diagnosed using faecal parasitological testing. Triclabendazole was the most reported treatment for fascioliasis, while praziquantel was the primary treatment for paragonimiasis, clonorchiasis, and opisthorchiasis. Low sensitivity of diagnostic tests as well as reinfection due to continued high-risk food consumption habits were common factors. Conclusion This review presents an up-to-date synthesis on the quantitative and qualitative evidence available for the 4 FBTs. The data show a large gap between what is being estimated and what is being reported. Although progress has been made with control programmes in several endemic areas, sustained effort is needed to improve surveillance data on FBTs and identify endemic and high-risk areas for environmental exposures, through a One Health approach, to achieve the 2030 goals of FBT prevention.